Analysis of The Application of Income Tax Calculations Under Section 21 Using The Average Effective Rate Approach (A Case Study of the Kendari City Regional Inspectorate) - Siti Nurhaliza; Andi Basru Wawo; Safaruddin Safaruddin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the implementation of Article 21 Income Tax calculations using the Average Effective Rate approach at the Kendari City Regional Inspectorate. The research employed a descriptive quantitative design and used a census sampling technique involving all 73 civil servants within the institution. Data were collected from payroll records, income reports, tax withholding documents, and structured interviews with personnel responsible for payroll administration. The analysis focused on evaluating the conformity of tax calculations with prevailing regulations, assessing the distribution of tax liabilities across employee categories, and examining the administrative implications of the Average Effective Rate system. The findings indicate that the calculation procedures were implemented in accordance with applicable tax provisions and generated consistent withholding outcomes. The results also show that the approach accommodates variations in employee income characteristics while maintaining proportional tax treatment. From an administrative perspective, the system simplified payroll processing procedures, reduced operational complexity, minimized correction requirements, and strengthened transparency and accountability in tax administration. The study concludes that the Average Effective Rate approach supports regulatory compliance, administrative efficiency, and the modernization of public sector financial governance.